CAVE GDP 2022 Photos - Cecotti, Marco (Cranfield University, 2022)
Just some pictures of the Group Design Project for the MSc in Connected and Autonomous Vehicle Engineering
Keywords: 'GDP'; 'CAVE'; 'Connected and Autonomous Vehicle Engineering'; 'Group Project'